The Changes of the Human Development on Micro-Regional and Settlement Levels - Katalin Lipták (DETUROPE)
The purpose of this paper is to define and estimate the human potential of the settlements in South-Cserehát,, Hungary. The human development index in the classical view can be estimated atmicroregional level with only hard distortions, to which the list of starting indicators differ from the usual indicators, such as GDP and GNI, the life expectancy at birth and the portion of taking part in education. However, the estimating calculations made for defining the human potential in a settlement level should be handled with hard restrictions , at the same time it perfectly shows the formation of the human factor in the region. As a research question the following was defined: In what range has the human potential changed on the basis of the census data and what kind of configuration changes have happened in the South-Cserehát? The aim of the study to attempt to estimate the HDI on settlement level.